Supervisi Pesantren di Indonesia - Devan Atha Dewangga Setiawan; Moh Hasan Romadhoni; Muhammad Nur Afdholun Mukarim (Ikatan Da'i Indonesia, 2026)
Pesantren are Islamic educational institutions that play a strategic role in character building, the development of Islamic knowledge, and community empowerment. In efforts to improve the quality of pesantren education, supervision serves as an important instrument implemented by the Ministry of Religious Affairs through the Directorate of Pesantren. This study aims to analyze the implementation of pesantren supervision in Indonesia, the institutional relationship between pesantren and the Ministry of Religious Affairs, as well as the duties and functions of the Directorate of Pesantren in guiding and supervising the administration of pesantren education. The research employed a literature review method by collecting and analyzing various scholarly sources, regulations, and relevant research findings. The results indicate that pesantren supervision encompasses both managerial and academic aspects aimed at improving governance quality, learning processes, educators’ competencies, and students’ welfare. The relationship between pesantren and the Ministry of Religious Affairs is synergistic within the framework of the national education system, whereby the government provides recognition, guidance, and facilitation for the implementation of pesantren education. The Directorate of Pesantren plays a strategic role in policy formulation, supervision implementation, monitoring, evaluation, and the development of educational quality and institutional capacity within pesantren. Therefore, pesantren supervision constitutes an essential instrument for fostering high-quality, accountable pesantren while preserving their distinctive characteristics as Islamic educational institutions in Indonesia.